Global Research Trends on Prosocial Behaviour: A Bibliometric Analysis - Zi Ning, Yi; Norashikin, Mahmud (UNIMAS Publisher, 2022)
This article describes a quantitative investigation of prosocial behaviour (PSB) research in bibliometric analysis. This bibliometric study focuses on the global research trends followed using Scopus Database. The main variables used for analyses of this study were by year, source, affiliation, author, country, area of a subject, and document type. The analysis of CiteScore, total publications, total citations, and h-index was done to rank the top contributors. The first research article on PSB was published in 1967, followed by the most recent publications in 2020. A total of 3,644 publications have been found during these 53 years. The author keywords and co-occurrences have been represented by bibliometric maps using VOSviewer 1.6.16. This study found an increase in the research trend for PSB, which was mainly published in seven (7) different publishers' journals. Amongst these, American Psychological Association, Wiley, and Frontiers are the three top publishers with 4.61%, 4.23%, and 4.21% contribution to the total publications. Findings regarding the top 15 most prolific authors showed that most of the authors related to PSB were from the United States, followed by Italy, Canada, and only one from Netherlands, Germany, and Chile. Further, most of the PSB research work was done in psychology. Overall, this study provides an evidence base, highlighting global trends and directions of research work published on PSB, adding value to the existing body of knowledge, and paving the way for future researchers.